Optimal timing and temperature for hyperthermic preconditioning in an animal model of fecal peritonitis - GÜLLÜOĞLU, MAHMUT BAHADIR (TAYLOR & FRANCIS INC, 2002)
The impact of immune parameters in the mechanism of hyperthermia is yet to be explained. In this study, the optimal timing and temperature of thermal treatment for reversing the abnormal immunologic parameters obtained in a rat model of peritonitis were planned to be determined. Male Sprague-Dawley rats were grouped as sham, control peritonitis, and thermally treated rats at the time of peritonitis or 4 h prior to induction of peritonitis both at 40 and 42degreesC. Peritonitis was induced by the cecal ligation and perforation model. Eight hours after the induction of peritonitis, rats were sacrificed and samples were taken for measurements of CD4+, CD8+, CD11b, B cells, NK cells, and tumor necrosis factor alpha (TNFalpha) and thiobarbituric acid-reactive substances (TBARS) levels. CD4+ expression and B cell amount were decreased whereas TNFalpha levels, CD8+ and CD11b expression, and NK cell amount were found to be increased in the control peritonitis group when compared to the sham group. Peritonitis induction also increased TEARS levels in liver tissue. Hyperthermic preconditioning at either 40 or 42degreesC applied 4 h prior to peritonitis induction returned all parameters to their normal levels, which is similar to the results of the sham laparotomy group. The results of TNFalpha values in preconditioned rats were varied according to the temperature that was applied. The levels were increased at 40degreesC, whereas they showed a decline at 42degreesC. Hyperthermic preconditioning prevented the oxidative damage in liver as well as TNFalpha elevation, particularly at 42degreesC. Results from this study suggest that hyperthermic preconditioning 4 h prior to the onset of septic events may improve the adverse outcome in sepsis.
Keywords: heat-shock proteins; hyperthermia; peritonitis; preconditioning; HEAT-SHOCK PROTEINS; LIPID PEROXIDES; LUNG INJURY; PROTECTS; THERMOTOLERANCE; CELLS; RAT; EXPRESSION; DISEASE; SEPSIS